Technology strategies - Smith, Cooper (Harris Kern's Enterprise Computing Institute (Series), 2002)
Suddenly, the business of technology and the technology of business have become one and the same. To succeed, managers, IT administrators, developers, and users need unprecedented clarity about the role of information technology. They need the long-term perspective that can only come with an in-depth understanding of how we got here, and where we're headed. Technology Strategies provides all that, and more. Cooper Smith, former Director of Technology at Nickelodeon Digital Lab and Animation Studios, shares insights that can improve every technology decision you make, professional and personal.